Valorización de subproducto de industria láctea a producción de etanol para bebidas alcohólicas - Ingaramo Carosi, Julia; Pirola, María Belén; Mainez, María Esperanza; Paez, Roxana Beatriz; Massera, Ariel Fernando (INTA, 2024)
Poster